Fall Armyworm Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae) in East Nusa Tenggara Province of Indonesia: Genetic Characterization and Strain Detection - Yustina Maria Silvia Wonga Puu; Itji Diana Daud; Andi Nasruddin; Melina Melina (Caraka Tani: Journal of Sustainable Agriculture, 2024)
Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae) is an invasive pest of corn plants spreading throughout the world, including East Nusa Tenggara (NTT), Indonesia. Despite the wide distribution, there is a lack of information on the strain or genetic diversity of the pest in NTT. Therefore, this study aimed to determine the strain of S. frugiperda from several areas in NTT with a molecular method using cytochrome oxidase subunit 1 (COI) and triose phosphate isomerase (Tpi) gene markers. The samples were collected from 3 islands: Timor, Flores, and Sumba. Amplification of the marker genes was carried out using 3 specific primers to identify the strain obtained from samples. Subsequently, polymerase chain reaction (PCR) products were sequenced and the DNA sequences were analyzed using the BioEdit and BLAST programs. Phylogeny analyses were carried out using the MEGA 11 program to verify the strain group of samples with reference isolates from other countries found in GenBank. The PCR results showed product amplicon size 811 bp for the CO1A marker. Based on phylogeny tree analysis using COI marker, S. frugiperda from NTT showed 2 clades, namely corn and rice strains. The characterization results showed that S. frugiperda in NTT comprised 63.6% corn and 36.4% rice strains. COIB classified S. frugiperda from NTT into the h4 haplotype subgroup, while Tpi gene marker was in the corn strain. This study provided valuable information regarding the strain of S. frugiperda in Indonesia to determine the appropriate control strategy.